Custo Brasil, gestão e desenvolvimento das indústrias de médio porte do Sudoeste do Paraná - Vedana, Gilmar Antônio (2017)
The high production costs in Brazil give rise to several debates. The present work has the objective of verifying the relation of the variables of Brazil Cost in the management and development of the medium-sized industries of the Southwest of Paraná. For this purpose, we worked on the theoretical framework the concept of Brazil Cost and its components: Logistics and Brazilian infrastructure; Brazilian Tax Charge; Labor Charges and Laws in Brazil; Electricity; Telecommunications; Interest (cost of capital); Bureaucracy; Corruption; And Instability of the currency; Industrial development in the context of regional development, highlighting the state industrial scenario and the Southwest Region of Paraná; And competitive strategies that can be developed by companies to remain competitive: variables strategic planning, intellectual capital, marketing, technology / innovation, quality, import, cost reduction, export, tax planning and partnerships / outsourcing. A quantitative approach was used with the use of regression and a qualitative approach concomitantly. The study was conducted with 32 industries from the Southwest of Paraná. The sample profile is predominantly in furniture sector, averaging 24 years of existence, generating almost 9,000 direct jobs and earning an average of R $ 27 million a year. With the research it was detected that the Brazilian Cost explains the variations of the national competitiveness variable, contrary to the findings of the literature, where the sample shows that raising the Brazil Cost increases the national competitiveness of the industries. It was verified that Brazil Cost in the sampling industries reaches 50.4% of its net revenue. The component that contributes most to the formation of the Brazil Cost is the tax burden and the one of smaller impact is the instability of the currency. It was also found that the variables marketing and cost reduction explain the variation in Brazil Cost, and, by investing in marketing, increases Brazil Cost and reducing costs automatically reduces Brazil Cost. Regarding the adoption of competitive strategies, it was understood that the sample industries invest in quality and cost reduction. The least used strategies are those related to foreign trade. It was noticed that the industries make use of several strategic actions but there is a very great range of strategies that are still not used and that could help in the development of the organization and to minimize the effects of the Brazil Cost.